TEACHING READING SKILLS TO FOREIGN LANGUAGE LEARNERS - Shnikulova Uldaulet Jumabaevna; Rzambetova Nadira Polatovna (Scholar Express Journal, 2024)
The article discusses one of the most important aspects of learning foreign languages - reading, which is both a goal and a means of teaching.
Keywords: foreign languages; speech activity; reading